PERLINDUNGAN HUKUM TERHADAP PENGENDARA YANG MENGAKIBATKAN HILANGNYA NYAWA SESEORANG YANG DISEBABKAN OLEH KELALAIAN KEDUA BELAH PIHAK DIJALAN RAYA - GITO SUTRIYO (Fakultas Hukum Universitas Narotama, 2022)
Research with the title Legal Protection of Riders Resulting in the Loss of a Person's Life Due to the Negligence of Both Parties on the Highway (Analysis of the Supreme Court Decision Number 2 / Pid.Sus / 2018 / PN.Mbo). Aiming to find out the legal settlement process against motorists who resulted in the loss of one's life due to negligence of both parties on the road and to find out the implementation of legal protection for motorists who resulted in the loss of one's life due to negligence of both parties on the road. This study uses the normative (normative) juridical method, namely research by observing and paying attention to the prevailing legal norms and being connected according to the facts of the problems in the study. The results of the research are the first, namely: the process of criminal justice settlement, investigation, prosecution, examination process in court. Second, namely: protection is the right of the suspect or defendant and the role of restoration of justise as an attempt by the suspect to be forgiven by the victim's family. Keywords: Legal Protection, Rider, Life, Negligence, Highway